What's in a Name? The Impact of Labels on Attitudes Toward Exonerees - Hamilton, Karli M.; Kukucka, Jeff; Allen, Erik; Clow, Kimberley A. (The Wrongful Conviction Law Review, 2024)
As exonerations have increased, so too has research into post-release challenges for wrongfully convicted individuals, including stigma, discrimination, mental illness, and inadequate support. In so doing, researchers and advocates have described this population in varied ways, which may elicit differing attitudes. To explore that possibility, 188 citizens read a tweet in which we varied the label ascribed to a newly released male prisoner (i.e., wrongly convicted, exonerated, innocent, or released/control), then reported their attitudes toward him. Contrary to expectations from the stereotype activation and labelling literature, different labels did not produce different judgements of the man’s character, criminality, or deservingness of support. Instead, perceptions were consistently more favourable for wrongfully convicted individuals (regardless of label) than other formerly incarcerated people (control). Troublingly however, the labels wrongly convicted, exonerated, and innocent still elicited some belief that the man was somehow involved in—or had committed—the crime for which he was erroneously convicted, that he may have committed other crimes in the past, and that he might commit crimes in the future. Implications are discussed in terms of stigma theory, growing media attention to wrongful convictions, and the disconnect between public and government support for post-exoneration services.